INVESTIGATION OF THE LATITUDINAL OCCURRENCE RATE OF EQUATORIAL PLASMA BUBBLE (EPB) AS A FUNCTION OF PRE-REVERSAL ENHANCEMENT (PRE) IN SOUTHEAST ASIA BASED ON IONOSONDE AND GPS RECEIVER OBSERVATION - Olla, Angelikus
This study aims to investigate the latitudinal occurrence rate of equatorial plasma bubble (EPB), as a function of pre-reversal enhancement (PRE) and the relationship between the EPB occurrence rate and the plasma background density. This study is done by analyzing ionosonde and GPS receiver data during equinox months (March-April) 2011-2014. The ionosonde located at Chumphon ?Thailand was used to estimate the PRE value. Thirty-nine GPS receivers in Southeast Asia (western part of Sumatran island) ranging from equator magnetic to magnetic latitude (MLAT) of 30°S were used to investigate the latitudinal occurrence rate of the EPB for the cases of strong and weak PRE. For the case of strong PRE, the occurrence rate of the EPB increases from 41.14% at the equator magnetic and reaches a peak of 53.30% at MLAT of 9°S, after that the occurrence rate of the EPB decreases and reaches 0.33% at MLAT of 28°S. Furthermore, for the case of weak PRE, the occurrence rate of the EPB increases from 19.54 % at the equator magnetic and reaches the peak of 24.96% at MLAT of 7°S, afterward the occurrence rate of the EPB decreases and reaches 0.39% at MLAT of 20°S. Generally, the findings above show that the latitudinal occurrence rate of the EPB for the case of strong PRE is higher than that for the case of weak PRE. There are differences in locations of the peak of EPB occurrence rate both for strong and weak PRE cases. For the case of strong PRE, the peak of EPB occurrence rate is located at MLAT of 9°S and the latitudinal extension of the EPB reaches MLAT of 28°S meanwhile, for the case of weak PRE, the peak of the EPB occurrence rate is located at MLAT of 7°S and the latitudinal extension of the EPB reaches MLAT of 19°S. The next finding is for the cases of strong and weak PRE, when the EPB formed, it always reaches MLAT of 10°S. Interestingly, this study also found that the higher of the ionospheric irregularities associated with EPB is located at the incline phase of the background plasma density (VTEC) enhancement.